PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI ASAM BASA - Fitri Refelita; Nur haliza; Yusbarina yusbarina; Neti Afrianis (Journal of Chemistry Education and Integration, 2026)
AbstractScience process skills are student abilities in applying scientific methods in understanding, developing science, and discovering knowledge.  Student science process skills were currently still relatively low so that an appropriate learning model was needed to overcome this.  This research aimed at finding out the effect of Problem Based Learning (PBL) model toward student science process skills on Acid Base lesson. This research was conducted at the second semester in the Academic Year of 2024/2025 to the eleventh-grade students of Chemistry at State Senior High School 12 Pekanbaru.  Quantitative method was used in this research with pretest-posttest non-equivalent control group design.  The samples of this research consisted of two classes, and they were selected with cluster random sampling technique.  The techniques of analyzing data were t-test to find out the effect of Problem Based Learning model toward student science process skills and determination coefficient test to find out the extent of the influence.  The research findings showed that (1) t-test produced the score of significance 0.000 lower than 0.05, and it meant that there was a significant difference between the experimental class and the control groups with the posttest mean score of science process skills in the experimental group 43.07, and the control group was 34.80, so H0 was rejected, and Ha was accepted; and (2) the determination coefficient test showed that the score of (r2) was 0.354, so it could be concluded that there was an effect of PBL learning model toward student science process skills on Acid Base lesson 35.4%. Keywords : Problem Based Learning, Science Process Skills, Acid-Base